(untitled) (Journal of Asian Development Studies, 2025)
Financial stability plays a crucial role in an individual’s overall well-being, influencing not only physical conditions but also psychological health. In today’s competitive world, financial hardship can significantly disrupt life satisfaction and increase mental health issues such as stress and anxiety. Although there is ample global literature on financial hardship, the educated cohort in the context of Pakistan has rarely been studied, particularly regarding perceived stress and anxiety. Therefore, this study aims to address this gap and offer practical implications. A cross sectional correlational research design was employed, using purposive sampling to collect data from 355 educated individuals (with a minimum qualification of a bachelor’s degree) who had been unemployed for at least one year. Participants were both men and women, aged between 22 and 35 years. To assess the study variables, three standardised instruments were used: the Economic Strain Scale, the Perceived Stress Scale, and the Beck Anxiety Inventory-II. It was hypothesised that financial hardship would be significantly and positively associated with both perceived stress and anxiety among educated cohort of Pakistan. Correlational proved the hypothesis of the study and the study’s hallmark was successfully achieved. Implications include the need for societal support systems, greater involvement of mental health professionals in raising awareness, and active governmental efforts to create employment.